Alternative To Development of Tourist Attraction with Public Private Partnership Scheme in Magelang Regency - Siti Arifah; Agung Nur Probohudono; Djuminah; Evi Gantyowati (Ilomata International Journal of Management, 2021)
This study aims to see how the condition of the object/Tourist Attraction (TA) in Magelang Regency in Indonesia and its alternative development. This research uses a descriptive qualitative approach with case studies of 31 tourism objects which will then be investigated regarding their conditions and possible future developments. Research data were obtained by direct observation of the location of tourist objects and through semi-structured interviews. The results of this study illustrate that tourism objects in Magelang Regency are currently quite developed. However, this has not been able to attract general tourists to linger in the regency and provided an optimal contribution to regional income. This is because tourism objects in the regency other than Borobudur Temple have not been maximized for their existence and utilization. The Public-Private Partnership (PPP) scheme model can be an alternative to be applied in developing tourism objects accompanied by an appropriate Value for Money (VfM) analysis. Tourism objects in the form of cultural heritage can be developed through concession contracts, natural beauty can be developed through management contracts, and artificial objects can be developed through service contracts while taking into account the development needs of each tourism object. Local governments need to establish cooperation with the private sector with a Public-Private Partnership scheme accompanied by the preparation of strict regulations so that the implementation of cooperation in the context of developing tourism objects in the Magelang Regency can bring optimal benefits to all parties.